A Review of the Leptodactylid Frog Genus, Odontophrynus - Savage, Jay M. (1965)
The frogs of the neotropical genus Odontophrynus form a distinctive and phyletically compact group of warty toadlike bur- rowers, readily distinguished from other members of the family Leptodactylidae. One wide-ranging species, Odontophrynus ameri- canus, is among the commonest amphibians in the drier subtropical regions of Argentina and adjacent portions of Bolivia, Brazil, Paraguay, and Uruguay. A second well-differentiated species, Odontophrynus cultripes, of southeastern Brazil and Argentina, is characterized by enormous dorsal poison glands. A third nominal form, Odontophrynus occidentalis, originally described from Territorio de Neuquén, Argentina, has been of questionable status. The present study was initiated by the rediscovery of Odontophrynus occidentalis from a number of localities along the eastern foothills of the Argentina Andes. Subsequently, in the course of investigations to establish the systematic position of the three known members of the genus, an undescribed species from northeast Brazil was discovered. The principal aims of this report are to review briefly the systematics and distribution of the four valid species of Odontophrynus, provide diagnoses for identification, describe the larvae of three of the forms, and describe the new Brazilian species. Detailed analysis of geographic variation and the ecology of O. americanus and O. occidentalis is reserved for a future paper by Cei. Barrio (1964) has recently discussed breeding calls and ecological characters in these two species.